2008
DOI: 10.1089/thy.2008.0255
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Enhanced Thy-1 (CD90) Expression in Orbital Fibroblasts of Patients with Graves' Ophthalmopathy

Abstract: Increased Thy-1 expression in GO orbital tissues and cultures is likely a consequence of the orbital disease process, reflecting both the presence of increased numbers of Thy-1-positive cells and higher expression on those cells. Adipogenesis itself does not appear to impact Thy-1 expression. Increased expression of this protein in GO could represent an adaptive response to cell injury, in effect limiting disease progression within the orbital adipose/connective tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 14 publications
(17 reference statements)
0
34
0
3
Order By: Relevance
“…This mechanism of lipid accumulation is distinct from that of adipocytes (37) and keratinocytes (32), and demonstrates the unique biology of the Thy-1 (1) lipofibroblast. Pulmonary fibroblasts seem to have biological characteristics distinct from myometrial or orbital fibroblasts, because the expression of Thy-1 in those tissues does not seem to stimulate lipid accumulation (46)(47)(48). A schematic depiction of the proposed mechanism for lipid accumulation in Thy-1 (1) pulmonary lipofibroblasts is presented in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism of lipid accumulation is distinct from that of adipocytes (37) and keratinocytes (32), and demonstrates the unique biology of the Thy-1 (1) lipofibroblast. Pulmonary fibroblasts seem to have biological characteristics distinct from myometrial or orbital fibroblasts, because the expression of Thy-1 in those tissues does not seem to stimulate lipid accumulation (46)(47)(48). A schematic depiction of the proposed mechanism for lipid accumulation in Thy-1 (1) pulmonary lipofibroblasts is presented in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well described that fibroblasts are heterogeneous, differing not only between organ systems but also within a given organ (25,(65)(66)(67)(68). We previously published that fibroblasts from the lung exhibit significant interindividual variability in their apoptotic response to cigarette smoke (69), a finding that may explain why only a fraction of smokers develop lung diseases, such as chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Valuesa are means ϩ SD, n ϭ 40; **P Ͻ 0.01. al. (21) published the results of a study in which they found Thy-1 mRNA and protein expression to be higher in orbital tissues and fibroblasts from TED patients compared with those from normal individuals. Therefore, TED patients are not at risk for increased orbital adipogenesis because of a deficiency of Thy-1-positive orbital fibroblasts.…”
Section: C677mentioning
confidence: 99%